Alternative Paradigm of Selective Vagus Nerve Stimulation Tested on an Isolated Porcine Vagus Nerve. (6th February 2014) - Pečlin, Polona; Rozman, Janez
Abstract : Alternative paradigm for spatial and fibre-type selective vagus nerve stimulation (VNS) was developed using realistic structural topography and tested in an isolated segment of a porcine cervical left vagus nerve (LVN). A spiral cuff (cuff) containing a matrix of ninety-nine electrodes was developed for selective VNS. A quasitrapezoidal stimulating pulse (stimulus) was applied to the LVN via an appointed group of three electrodes (triplet). The triplet and stimulus were configured to predominantly stimulate the B-fibres, minimizing stimulation of the A-fibres and by-passing the stimulation of the C-fibres. To assess which fibres made the most probable contribution to the neural response (NR) during selective VNS, the distribution of conduction velocity (CV) within the LVN was considered. Experimental testing of the paradigm showed the existence of certain parameters and waveforms of the stimulus, for which the contribution of the A-fibres to the NR was slightly reduced and that of the B-fibres was slightly enlarged. The cuff provided satisfactory fascicle discrimination in selective VNS as well as satisfactory fascicle discrimination during NR recording. However, in the present stage of development, fibre-type VNS remained rather limited.